Effective First Impressions Online: A Case Study of Working With Industry Professionals to Analyze Web Site Usability - Emily Rhoades; Katie Chodil; Tracy Irani (Journal of Applied Communications, 2007)
The Internet has opened doors for communicators, giving them new ways to reach a variety of audiences in an unfiltered and timely fashion. However, good Web site design is complex, and an unfriendly or confusing site can easily intimidate or discourage users. This paper describes a recent partnership between researchers in academia and an agricultural organization whose aim is to educate the public about the agricultural industry. Together, they used current usability testing methodology to determine the effectiveness of the organization's Web site. This paper presents the results of the study as well as recommendations for individuals considering such a partnership.